VD_FINDINFO Décision / 2012 / 778 vom 8. Juni 2012 - VD Tribunal cantonal (2012)
RISQUE DE FUITE, RISQUE DE COLLUSION, RISQUE DE RÉCIDIVE, DÉTENTION PRÉVENTIVE | 221 CPP (CH), 393 al. 1 let. c CPP (CH)